Effect of ultrasonication duration of polyvinyl alcohol (PVA) gel on characterizations of PVA film - Abral, Hairul; Atmajaya, Arief; Mahardika, Melbi; Hafizulhaq, Fadli; Kadriadi; Handayani, Dian; Salit, Mohd Sapuan; Rushdan, Ahmad Ilyas (Elsevier, 2020)
Many works reported a PVA based film prepared using ultrasonication, however, information on the effect of this treatment on changes of PVA’s properties is still limited. The main objective of this work was to study the effect of ultrasonication duration on the properties of PVA film. The PVA gel was sonicated using a 360 W ultrasonic probe for 2.5, 5, 7.5 and 10 min. Ultrasonication duration for 7.5 min results in a significant effect (p ≤ 0.05) on an increase in tensile strength, but not on tensile modulus and strain at the break of the film. After this vibration duration, tensile strength increased by almost 29 %, strain at break decreased by 30 %, opacity decreased by 22 %, and water vapor permeability decreased by 11 %. On the other hand, moisture resistance decreased significantly (almost 12 %). The sonicated film underwent larger lattice strain and had higher crystal structure compared to non-sonicated film. This work informs that ultrasonication on PVA gel is a potential method to fulfil some properties of PVA film for food packaging material.